Low‐Intervention Birth Suites Within a Community Hospital: An Innovative Approach to Perinatal Services. (22nd February 2021) - Javernick, Julie A.; Dempsey, Amy; DeLeon, Betsy
Abstract: Perinatal care leaders at a community hospital located in the Denver, Colorado metropolitan area searched for an innovative way to provide a low‐intervention option that promoted physiologic birth for women seeking intrapartum care. This reasonably priced project focused on the transformation of traditional labor and delivery rooms into birth suites and included installation of birth slings, full‐size beds with home‐like mattresses, new sleep sofas for the partners, and the removal of computer screens and electronic fetal monitors. In addition, the team wrote a specific birth suite policy, provided nurse education focused on intermittent auscultation and labor support techniques, and developed a birth suite curriculum for patient education. This innovative model of care demonstrated outcomes similar to those seen in community‐based birth centers and received positive feedback from families who labored and gave birth in these suites. In the instance when the birth suite is no longer the appropriate environment for intrapartum care secondary to risk factors, a woman's preference, or obstetric emergency management, this model allows for expeditious transfer of the woman or newborn to a location where an appropriate higher level of care can be provided. Converting 2 labor and delivery rooms to low‐intervention birth suites required minimal funding and enabled a community hospital in Colorado to expand its perinatal services to women who are seeking low‐intervention birth options that promote physiologic birth.